Vpliv filozofske misli skozi zgodovino na družbeno konstrukcijo smrti - Štrancar, Klelija (Obzornik zdravstvene nege, 2006)
Thinking about death was rather suppressed in last decades in the western civilization. Death retreated from public space to the private one as something horrible and senseless. But it was not always like that. Death formed part of everyday life, so people talked and thought about it. Thereforewe are wondering whether contemporary people''s running away from death is not actually fleeing the reality of life itself? And does not life itself become absurd, senseless and worthless in the light of death? In fact we are talking about the essential question in our lives, and the confirmationor the rejection of the meaning of our existence depends on it. With other words, what should our life and lives of other people mean from theperspective of death and dying? Human beings are being built by memories. Memories are history. If we want to understand our present, we have to build it on our memories - history. If we do not care about history, we are not onlydeprived of past, but also of present and future. Health workers need a radical revision of the issue of death and dying. Orientation of our action regarding other people depends a great deal on this issue. ln this way also our responsibility and sensibility in the field of caring, which is the essence of health care.
Keywords: Attitude to death; Death; filozofija smrti; Philosophy; smrt; umiranje